Dissociative experiences reduce online problem gambling treatment effectiveness - Korvuo Tuire; Palomäki Jussi; Castrén Sari (Elsevier, 2025)
Aims
To determine whether dissociative experiences moderate online problem gambling treatment effectiveness, and to characterize the temporal persistence of the relationship between dissociation and problem gambling.
Design
Repeatedly measured self-report data on a guided online cognitive behavioral therapy for problem gambling collected on four occasions: before treatment, after treatment, and at 6- and 12-month follow-ups.
Setting and participants
The data (N = 1243, 59.2% males) were collected in Finland between 2019 and 2021.
Measurements
The primary outcome variable was the self-reported level of problem gambling. The predictors were the treatment phase and dissociative experiences, their interaction, and the demographic covariates of age, education, income, and gender.
Findings
Problem gambling scores and dissociative experiences declined significantly following treatment and remained low through the follow-ups (retention rates: 52.6% [post-treatment], 26.3% [at the 6-month follow-up], and 16.1% [at the 12-month follow-up]). However, the treatment was significantly less effective in reducing problem gambling for individuals who kept experiencing dissociation after the treatment.
Conclusions
Dissociation is an integral sign of problem gambling severity and sustained dissociative experiences may significantly reduce the long-term effectiveness of online problem gambling treatments. Treatment efforts should be customized to account for individual differences in dissociative tendencies, and future research should broaden the study of dissociative experiences to other behavioral addictions.